2022
DOI: 10.1002/prep.202100145
|View full text |Cite
|
Sign up to set email alerts
|

Combustion Behavior of the Inorganic Nitrates‐Based Compositions. Part II: Effect of Al and Al‐Mg Alloy on Burning Rate

Abstract: The influence of metallic fuel (aluminum and aluminum‐magnesium alloy) on the burning rate of compositions based on inorganic nitrates (KNO3, NaNO3, CsNO3, Ba(NO3)2, Sr(NO3)2) was studied in a wide range of pressure (0.1–18 MPa). Samples have the same binder and differ in basic burning rate and flame temperature. Calculated flame temperature greatly depends on the Al and Al−Mg amount. The effect of metallic fuel on the burning rate of basic samples is complex. It depends not only on the properties of metals bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
(34 reference statements)
0
2
0
Order By: Relevance
“…Experiments have shown that this also applies to the combustion catalysis of trinitrophenol 25 . Previously, 26,27 it was assumed that leading combustion zone for double‐base propellants with catalysts is the c‐phase reaction layer, even if the catalysts have an effect in the gas zone, based on the thermal balance of the c‐phase data.…”
Section: Resultsmentioning
confidence: 99%
“…Experiments have shown that this also applies to the combustion catalysis of trinitrophenol 25 . Previously, 26,27 it was assumed that leading combustion zone for double‐base propellants with catalysts is the c‐phase reaction layer, even if the catalysts have an effect in the gas zone, based on the thermal balance of the c‐phase data.…”
Section: Resultsmentioning
confidence: 99%
“…For example, double base propellants, even with a high content of nitroglycerine (to 50 -70 %), burn at a speed of 0.9 -1.2 mm/s; gunpowder based on diethylene glycol dinitrate does not burn. In our previous work KNO 3 -based compositions with oxidizer excess coefficient (α) have an increased ability to burn at atmospheric pressure [20,21]. For most studied KNO 3 -based samples in [20], the dependence of burning rate on pressure consists of two sections: in the first section, the value of n is 0.06 -0.28, and in the second section, the value of n is much higher: 0.47 -1.56.…”
Section: Resultsmentioning
confidence: 99%
“…The use of Mg alloys has become an effective mean [8][9][10]. Among them, Al12Mg17 has low melting and boiling point, and Mg in Al12Mg17 can be rapidly vaporized when burning [11]. Moreover, Al12Mg17 has low ignition temperature, stable combustion performance, and the addition of aluminium can improve the energy density of Al12Mg17 [12][13][14].…”
Section: Introductionmentioning
confidence: 99%